PENGARUH PELAKSANAAN TUNJANGAN TAMBAHAN PENGHASILAN TERHADAP PENINGKATAN KINERJA PEGAWAI DI LINGKUNGAN BADAN KEPEGAWAIAN DAERAH KOTA SAMARINDA - SANTI, DEWI (PREDIKSI, 2016)
While this is going Pros And Cons Income Supplement Allowance Problems in some SKPD Samarinda City Government. Since in charge Mayor Regulation No. 2 Year 2013 About Benefit Supplement Income to Civil Servants, It is crowded at the talk, because all the civil servants who are SKPD Samarinda City Government was pleased to get the attention of the government of Samarinda. Rules on the additional income local officials should be evaluated for being one of the contributors to the problems in the local budget allocation.In this study, it can be seen Objectivity Service Performance Officer and Regional PNS After Earned Income Supplement benefits that apply to employees in the Environment Regional Employment Board of Samarinda and how Allowance Income Supplement Fit Workload Regional Employment Board Samarinda.Minister Regulation No. 59 Year 2007 on Article 39 of the Regulation of the Minister of the Interior shall be declared that the provision of additional income to the employee may be granted based on workload, work performance, lack of professional and other objective considerations.In fact, it is not always the case that with the increase in workload performance will be decreased. Performance may be affected by the work load if the load is defined too high or too low. Basically, civil servants already earn rewards based on class rank and position in the form of a basic salary and allowances. The assumption that an employee will do the work - the daily routine tasks and offices with the number of working hours start at 07.30 until 16.00 minus prayer and meal breaks for 1 hour during the day (for a total of 7.5 hours a day).Things need to be done to equalize fringe benefits employee income is: a). Eliminating honor-honor projects and activities in the District Government or the Provincial Government; b). Collecting honor-honor scattered throughout offices / agencies within the government; c). Proportionally distribute the honor-honor to all employees; d). Counting the number of honor-honor in all departments / agencies shared